Training interventions enhance interns’ performance, skills, and workplace readiness in organizational settings - I Made Sura Ambara Jaya; Luh Mei Wahyuni; Muhammad Ahmad Mazher; Md. Afsarul Islam; Muhammad Waheed (Journal of Commerce, Management, and Tourism Studies, 2026)
Internship programmes are a critical bridge between academic learning and workplace performance, yet their effectiveness depends heavily on the quality of training and development provided to student interns. This study aims to examine how structured training, ongoing development activities, and performance feedback influence interns’ task performance, soft skills, and readiness for employment. Using a mixed-method design, quantitative survey data from internship students and workplace supervisors are complemented by qualitative interviews exploring perceptions of training content, supervision quality, and learning climate. Quantitative data will be analysed using descriptive statistics and regression to test relationships between training practices, learning outcomes, and performance ratings, while thematic analysis will be applied to interview transcripts to identify patterns in interns’ learning experiences. The study is expected to show that clearly designed training, mentoring, and continuous evaluation enhance interns’ technical competence, soft skills, and problem‑solving efficacy, thereby improving overall internship performance and employability. Findings will inform higher education institutions and host organizations in designing evidence‑based training frameworks that maximise the developmental impact of internship programmes.